2013
DOI: 10.1007/s00264-013-2098-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of augmented and nonaugmented primary repair of the anterior cruciate ligament: an in vivo animal study

Abstract: Purpose The purpose of this study was to evaluate in a sheep model the biomechanical performance of augmented and nonaugmented primary repair of the anterior cruciate ligament (ACL) following transection at the femoral end during a 12-month postoperative observation. Methods Forty sheep were randomly assigned to nonaugmented or augmented primary ACL repair using a polyethylene terephthalate (PET) band. At two, six, 16, 26 and 52 weeks postoperatively four sheep in each group were sacrificed and biomechanical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…Histologically, the augmented group showed more granulation tissue at 2 weeks, increased vascularity at 6 weeks, more fibroblasts and collagen at 16 weeks, more normalappearing collagen alignment at 26 weeks, and welldefined longitudinally oriented collagen fascicles with sparse cellularity at 52 weeks. In their follow-up study using the same model, Seitz et al 24 PRIMARY REPAIR OF ACL alone. They found that beginning at the 16-week time point, the PET-augmented primary repair group showed less instrumented laxity and greater tensile strength and ligament stiffness than the group that underwent suture repair alone (P < .05).…”
Section: Preclinical Studiesmentioning
confidence: 95%
“…Histologically, the augmented group showed more granulation tissue at 2 weeks, increased vascularity at 6 weeks, more fibroblasts and collagen at 16 weeks, more normalappearing collagen alignment at 26 weeks, and welldefined longitudinally oriented collagen fascicles with sparse cellularity at 52 weeks. In their follow-up study using the same model, Seitz et al 24 PRIMARY REPAIR OF ACL alone. They found that beginning at the 16-week time point, the PET-augmented primary repair group showed less instrumented laxity and greater tensile strength and ligament stiffness than the group that underwent suture repair alone (P < .05).…”
Section: Preclinical Studiesmentioning
confidence: 95%
“…Next to ACL healing studies that transect the ACL in its midsubstance there are studies that transect the ACL at its Chapter 10 femoral insertion site. (121,134) The results of these studies demonstrate that the ACL has also a healing response at the femoral insertion site.…”
Section: Bio-enhanced End-to-end Acl Repairmentioning
confidence: 94%
“…Một dụng cụ cố định động bên trong gân (DIS) đã được phát triển nhằm buộc hai đầu Dây Chằng Chéo Trước đứt trong khi giữ gối trong tư thế chuyển dịch ra sau cố định. (121,134).…”
Section: Nối Tận Tận Dây Chằng Chéo Trước Với Tăng Cường Sinh Họcunclassified
“…The clinical results achieved by ACL reconstruction are generally accepted. Nevertheless evident problems are well known, such as graft failure, donor site morbidity, loss of proprioception and the inexact anatomical form of reconstruction 6,7 . In addition, despite subjective and objective joint stability following reconstruction, the risk for posttraumatic arthritis remains [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Only recently, primary ACL repair has regained increasing research interest. A number of preclinical studies demonstrated the potential role of primary repair in combination with modern surgical techniques and enhancing bioactive materials 7,[11][12][13] . Taylor et al mentioned that despite the reported unacceptable high failure rates of previously published clinical studies, there constantly was a subset of patients that met the criteria for clinical success 14 .…”
Section: Introductionmentioning
confidence: 99%